2006
DOI: 10.1002/jcp.20815
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 negatively affects the survival/maturation of cord blood CD34+ hematopoietic progenitor cells differentiated towards megakaryocytic lineage by HIV‐1 gp120/CD4 membrane interaction

Abstract: To investigate the mechanisms involved in the human immunodeficiency virus type 1 (HIV-1)-related thrombocytopenia (TP), human umbilical cord blood (UCB) CD34(+) hematopoietic progenitor cells (HPCs) were challenged with HIV-1(IIIb) and then differentiated by thrombopoietin (TPO) towards megakaryocytic lineage. This study showed that HIV-1, heat-inactivated HIV-1, and HIV-1 recombinant gp120 (rgp120) activated apoptotic process of megakaryocyte (MK) progenitors/precursors and decreased higher ploidy MK cell fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…25,26,28 This disruption in the bone marrow microenvironment causes a loss of colony-forming cell growth, and disrupts proper hematopoietic lineage differentiation. 25,29,30 Work by multiple groups has shown that hematopoietic function can be at least partially restored with the use of highly active antiretroviral therapy (HAART). [31][32][33][34][35][36][37] The findings described here indicate that HIV-1C can infect HPC-CFUs and CD34 ϩ HPCs in vitro and in vivo, and that this infection is associated with higher anemia rates in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,28 This disruption in the bone marrow microenvironment causes a loss of colony-forming cell growth, and disrupts proper hematopoietic lineage differentiation. 25,29,30 Work by multiple groups has shown that hematopoietic function can be at least partially restored with the use of highly active antiretroviral therapy (HAART). [31][32][33][34][35][36][37] The findings described here indicate that HIV-1C can infect HPC-CFUs and CD34 ϩ HPCs in vitro and in vivo, and that this infection is associated with higher anemia rates in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the findings from the studies on the liquid cultures showed induction of apoptosis in the megakaryocytic progenitors exposed to dengue 2 virus and within a differentiation window of five days. Interestingly, induction of megakaryocyte apoptosis in vitro has been reported for other viruses like HIV-1 (Gibellini et al, 2007) and African swine fever virus (Gomez-Villamandos et al, 1998), where it has been proposed to be a major factor contributing towards thrombocytopenia associated with these infections. Further indepth studies are required to examine dengue virus-induced apoptosis of megakaryocytes based upon the present observations in order to elucidate its role as a factor affecting thrombopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with reports that TGFβ can directly arrest megakaryocyte maturation 13 and supports a dual role for TGFβ in platelet decline during asymptomatic infection, with TGFβ inhibiting megakaryocyte development and therefore decreasing platelet numbers both indirectly by decreasing the production of THPO and directly through TGFβ-mediated maturation arrest in megakaryocytes. Decreased megakaryocyte differentiation/maturation or defective platelet production secondary to direct lentiviral contact or infection may also contribute to decreased production 21,34 . Other mechanisms, such as platelet destruction secondary to platelet autoantibodies raised versus homologous lentiviral envelope proteins and sequestration of activated platelets in leukocyte-platelet aggregates, also have the potential to contribute to platelet decline 22,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar elevations in plasma TGFβ level have been previously noted in HIV-infected patients compared with healthy controls, and associated with the progression of disease. 37 HIV-1 gp120 or Tat are sufficient to stimulate the production of TGFβ from hematopoietic stem cells or mammary epithelial cells in culture, respectively 21,38 . cART serves to suppress lentiviral replication and has been previously reported to decrease the level of TGFβ transcription in the lymph nodes of SIV-infected macaques 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation